Ethics in culture the dissemination of values through literature and other media - Erll, Astrid; Grabes, Herbert; Nünning, Ansgar (Spectrum Literaturwissenschaft, 2008)
Alongside the recent cultural turn in the humanities, there has been a noticeable return to ethical considerations. With regard to literature as well as other media, this has rekindled awareness of a tension, antagonism, or even disparity between ethics and aesthetics.This volume of articles takes a more systematic and cross-disciplinary approach to the widely mooted ethical turn in literature and other media than has been pursued so far. It brings together a wide range of critical perspectives from literary studies, media and cultural memory studies, and philosophy, tracing the complex and sometimes conflicting relationship between ethics and aesthetics in theoretical contexts and individual case studies as diverse as colonial architecture, nineteenth-century literary histories, and postmodern writing and art.
Keywords: Literature and morals; Ethics (in literature); cultural studies; values (in literature)